Upaya Meningkatkan Kemampuan Pemecahan Masalah pada Mata Pelajaran Matematika Melalui Model Pembelajaran Problem-Based Learning Peserta Didik Kelas V - Sari, Puspita Maya; Wahyana , Antonius (Papanda, 2025)
Education is one of the important factors in improving the quality of human resources in a country. This study was motivated by the low problem-solving ability in Mathematics subjects of grade 5 students of SDN Tegalrejo 04 Salatiga. This study is a classroom action research with the aim of improving problem-solving abilities through the Problem Based-Learning learning model using a model developed by Kemmis and MC. Taggart. The data collection techniques used were interviews and written tests. The instruments used were interview guidelines and assessment question sheets. Data analysis conducted in this study was quantitative data analysis and qualitative data analysis. The indicators of success in this study include 1) if the results of the problem-solving ability test have been completed to reach a value of ≥ 70 classically, 2) if the results of the problem-solving ability test of students have been completed to ≥ 75% classically. The results of this study increased from the pre-cycle reaching 31.25%, cycle I reaching 50%, and cycle II reaching 81.25%. Based on these data, this study shows that the problem-based learning model is able to improve the problem-solving abilities of grade 5 students.